2018
DOI: 10.1007/s13595-018-0773-z
|View full text |Cite
|
Sign up to set email alerts
|

Xylogenesis of compression and opposite wood in mountain pine at a Mediterranean treeline

Abstract: & Key message Comparisons between compression and opposite wood formation in prostrating Pinus mugo indicate that the secondary meristem can produce more tracheids with thicker walls by also increasing the number of contemporaneously differentiating cells, rather than only increasing the duration or the rate of cell formation. & Context Although cambium tissues within a stem experience the same climatic conditions, the resulting wood structure and properties can strongly differ. Assessing how meristem differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Several past studies reported that intra-annual xylem formation follows a sigmoid curve [32,33,36,37,48,49,53,62,73]. This intra-annual dynamics of wood-formation was confirmed as well in our study of coniferous tree species growing at a subalpine site in the Republic of Korea.…”
Section: Intra-annual Variations Of the Number Of Cells In The Cambiusupporting
confidence: 89%
See 1 more Smart Citation
“…Several past studies reported that intra-annual xylem formation follows a sigmoid curve [32,33,36,37,48,49,53,62,73]. This intra-annual dynamics of wood-formation was confirmed as well in our study of coniferous tree species growing at a subalpine site in the Republic of Korea.…”
Section: Intra-annual Variations Of the Number Of Cells In The Cambiusupporting
confidence: 89%
“…beginning and end of May (DOY 124-146) ( Table 2). Based on these observations, it was verified that A. koreana (three in five trees), P. koraiensis (one in five trees), and P. jezoensis (one in five trees) required at least 73 Table 2). The cambium cells are vulnerable meristematic tissues under cold condition [39].…”
Section: Effects Of Degree-day (Dd) On Triggering the Cambial Activitymentioning
confidence: 80%
“…Nevertheless, at the highest elevation in PE, the positive correlation between RWI and maximum temperatures in October of the current and previous year would suggest that an elongation of the growing season may occur, with consequent increase in stem radial growth. Palombo et al (2018), at the tree line on the Majella Massif, observed that the growing season can be consistently longer compared with Alpine environment, lasting from May to October. Dolschak et al (2019), modeling the water balance of European beech stands, along a gradient of declining annual precipitation, observed that an increase in stand productivity, caused by longer assimilation periods under optimal conditions, could be counterbalanced by soil moisture deficit in the middle of summer.…”
Section: Discussionmentioning
confidence: 97%
“…The prostrate habit of mountain pine results in a dense and impenetrable cover mat over the whole area; the main difficulty was to distinguish individual stems from the branches. Mountain pine trees were cored close to the base of the trunk and on the cross-slope side of the trunk to avoid sampling on branches and compression wood (Palombo et al 2018). European beech trees were sampled at breast height (1.3 m).…”
Section: Tree Ringsmentioning
confidence: 99%
“…The two species (C. fortunei and C. lanceolata) included in this study started growing between March and April, while temperate and boreal conifer species started in April-May (Cuny et al, 2015;Rossi et al, 2016;Chen et al, 2019). Mediterranean species started between late March and early May (Camarero et al, 2010;Palombo et al, 2018;Antonucci et al, 2019). C. fortunei and C. lanceolata stopped growing from October to November (Camarero et al, 2010;Vieira et al, 2014;Antonucci et al, 2019).…”
Section: Climatic Control On the Onset And Termination Of Cambial Activitymentioning
confidence: 99%